The role of adenosine in remote ischaemic conditioning - Contractor, H (2012)
Strategies to reduce infarct size in ischaemia-reperfusion (IR) syndromes such as acute myocardial infarction are of high clinical and scientific interest. Remote ischaemic preconditioning (rIPC) is one such strategy but its mechanisms remain incompletely understood. Multiple lines of evidence from animal studies suggest that the endogenous purine nucleoside adenosine is a key mediator of preconditioning pathways but no evidence exists as to adenosine’s role in the more complex physiology of humans. The work in this thesis aims to elucidate the role of endogenous adenosine in the physiological phenomenon of rIPC and to examine the role of exogenous adenosine in triggering preconditioning-like states. In a randomised, placebo controlled study using healthy volunteers and the human forearm model of ischaemia-reperfusion injury, I demonstrate that delivery of the adenosine receptor antagonist caffeine, prior to the initiation of a rIPC stimulus abrogates the protective effect of rIPC on IR. By then selectively infusing caffeine to achieve high local but low systemic concentrations, I also demonstrate that adenosine receptor activation is important in the ‘trigger’ phase of rIPC rather than in the ‘effector’ phase and that blockade of the trigger phase effectively inhibits the release of a circulating humoral protective factor. These studies provide evidence of the crucial role of adenosine receptor activation in human rIPC, demonstrating their sites of action and illuminating their potential mechanism of action. To study whether exogenously delivered adenosine can recapitulate preconditioning-like states, in initial studies in a large mammal model of acute myocardial infarction, I demonstrate that adenosine, given after the onset of ischaemia, but prior to reperfusion, significantly reduces myocardial infarct size. In a subsequent study, translating these findings to humans with coronary disease, I demonstrate that the delivery of adenosine in a range of concentrations is able to illicit the release of a circulating preconditioning factor which is transferrable across species and can reduce infarct size in a murine model of myocardial IR.